Development and Analysis of a Game Design Methodology applied to the Game Honor Keeper Conception - Vitor, Ikaro Siqueira Rodrigues; Rodrigues, Elisa de Cássia Silva; Batista, Bruno Guazzelli (Journal on Interactive Systems, 2024)
Game design is a challenging activity that necessitates expertise and competencies from various domains. Teaching new designers involves grasping and implementing methodologies, integrating them into a particular design context, which proves to be a demanding yet essential task. In this paper, we report an experience in the conception of a game where two methodologies were analyzed and combined to describe a process with well-defined sequential activities. To verify the results with the application of this methodology, the developed game was made available for testing with real users, together with a questionnaire that sought to analyze the players’ level of satisfaction with the main aspects of the game. Based on the feedback and examination of responses from test participants, it was evident how adjusting and implementing the method positively influenced the game project in an organized and unified manner, leading to a favorable reception from users.